Isotherm and Adsorption Thermodynamics Cross-Linked Chitosan Microcapsules of Kalium Pershulphate to Methyl Orange Dye - Endang Sulistyawati; Heni Anggorowati; Nadia Rochmah K.P; Navyta Ariardini (Eksergi, 2022)
Modeling of isotherm and adsorption thermodynamics in this study, leads to the determination of the classification of adsorption isotherms and the determination of the amount of energy and entropy to determine the impeccability of the process. As an adsorbent, a potassium persulfate crosslinked chitosan microcapsule was synthesized through a microencaptulation process using a solvent evaporation method with a carboxy methyl cellulose CMC coating. The characteristics of the chitosan microcapsules that were formed had a degree of deacetylation of 53,92 %, and a bn mutant diameter around 1-100 µm. Test materials used azo methyl orange dyes, which are often found in industrial waste and laboratory waste. Observations were made with variations in the concentration of methyl orange solution 5, 7,5, 10, 12,5, 15, 17,5 and 20 ppm at temperatures of 30, 40 and 50 ° C. The calculation results show that the adsorption isotherm model obtained approaches the Langmuir isotherm model. The results of the analysis of temperature effects obtained positive Gibbs energy change values (ΔG) so that the adsorption process takes place non-spontaneously. The values of  enthalpy change (ΔH) and entropy change (ΔS) of 33,86 kJ / mol and 0,0899 kJ / mol.K.  This indicates that adsorption occurs chemically adsorption, is endothermic and adsorbat is not completely adsorbed.